“It’s Creative Stuff!” The REF Impact Agenda and the Discursive (Re)Positioning of Academics - Angermuller, Johannes; Wroblewska, Marta (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
The higher education sector is increasingly subject to formal evaluation practices. Individuals, institutions and entire systems are assessed, evaluated and ranked by actors from the public and private sectors. Existing research often focuses on the goals, values and criteria of academic evaluation. In this article, however, we discuss evaluation as a discursive practice consisting of academics positioning themselves across different social arenas. Closer scrutiny will be applied to the evaluation of (extra-academic) impact as defined by the British Research Excellence Framework (REF). Based on interview data collected in the context of REF 2014, we analyse how academics negotiate their subject positions linguistically and socially across different academic arenas. As positioning experts, academics respond to the challenges of institutional evaluation by switching between different and often contradictory logics. We present both the theoretical background – social perspectives on polyphonic subjectivity – and a methodological approach to evaluation as a practice of positioning and repositioning by academics in the social world of academia.